O facebook como ferramenta pedagógica no ensino de História - PANTOJA, Bruno Amorim (Universidade Federal do Pará, 2019)
The dissertation proposes to discuss the relationship between the teaching of history and the New Technologies of Information and Communication (NTIC),since it is a reality the dissemination of technologies in the so-called information society, where the internet, and especially social networks, as well as "old" technologies such as TV and radio, generate a bombardment of information and with the interlocution of teachers, these technologies can be allied in the process of teaching and learning, generating an interaction in the classes and an interest in the content taught. The thematic clipping of the research work will be done with the use of Facebook as a pedagogical resource in teaching history to two classes of elementary school in a private school in Belém do Pará. The intention will be to understand if these tools can help the teacher of History, and thus demonstrate that this tool, through the intermediary of the educator can dynamize the process of teaching and learning, leaving lessons more interesting for students and energizing the process of building historical knowledge. For this to be possible, a methodology called Investigative Thematic Unit or also known as workshop class will be used, where several steps are followed in the construction of historical knowledge with students, where the first step is to investigate the students' previous knowledge. The product to be generated will be a closed group, in the social network Facebook, that will function as a repository of videos, images, texts, historical Memes and etc. In addition, it will be a space for debates and discussions about images, gifs, videos, exercises and tests questions, all this, posted by the teacher, referring to the subjects chosen by the students, which will be contained in the curriculum of the class, in the case of the ninth year of Elementary Education.